Noise Exposure in the Workplace, Genetic Susceptibility, and Incidence of Atrial Fibrillation: A Prospective Cohort Study - Wenzhen Li; Junjie Zhu; Xingjie Hao; Zhaomin Chen; Dongming Wang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background No study explored the association of noise exposure in the workplace and genetic susceptibility with incidence of atrial fibrillation (AF). We aimed to assess the separate and joint relationship of noise exposure in the workplace and genetic susceptibility with the risk of AF. Methods and Results We included 167 577 participants without AF at baseline in UK Biobank. Cox proportional hazards models were used to assess the separate and joint association of noise exposure in the workplace and genetic susceptibility with the risk of AF. During a median follow‐up of 11.83 years, we observed 9355 AF cases. Compared with no noise exposure in the workplace, the hazard ratios (HRs) and were 1.08 (95% CI, 0.99–1.18) for noise exposure in the workplace of <1 year, 1.03 (95% CI, 0.95–1.12) for noise exposure in the workplace of around 1 to 5 years, and 1.08 (95% CI, 1.02–1.14) for noise exposure in the workplace of >5 years, respectively, after adjusting for potential confounders. Genetic risk was positively associated with AF, compared with low genetic risk (tertile 1), the HRs were 1.50 (95% CI, 1.41–1.59) for medium genetic risk (tertile 2) and 2.51 (95% CI, 2.38–2.65) for high genetic risk (tertile 3). However, no interaction between noise exposure in the workplace and genetic susceptibility was observed (P>0.05). Conclusions Long‐term noise exposure in the workplace is positively associated with a higher incidence of AF regardless of genetic background.